INVASIVE CORTICOTROPH PITUITARY MACROADENOMA: CASE REPORT AND LITERATURE REVIEW - Kosumphan, Kamila; Thaweboon , Burasakorn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 57-year-old Thai female presented with severe hypertension and generalized edema 5 months ago. She developed proximal muscle weakness, and bitemporal hemianopia 2 months prior to admission. She had moon facies, facial plethora and purplish abdominal striae. In addition, she had accentuated hyperpigmentation on the skin creases and knuckle areas. Biochemical results were compatible with adrenocorticotropic hormone (ACTH)-dependent Cushing’s syndrome. Magnetic resonance imaging demonstrated a 5.9 x 5.1 x 6.7 cm pituitary macroadenoma, extending to the cavernous sinus and left optic tract. Transsphenoidal pituitary tumor resection was performed. Histopathology confirmed a pituitary adenoma with positive staining for ACTH and somatostatin. Follow-up MRI showed residual tumor, hence adjuvant radiotherapy was given. Based on the 2022 PitNET WHO classification, she is categorized as having an invasive and non-proliferative corticotroph pituitary tumor. Three years after surgery, there was still no evidence of tumor progression.